BOKO HARAM'S TERRORIST CAMPAIGN IN NIGERIA contexts, dimensions and. - Oriola, Temitope B.; Onuoha, Freedom; Oyewole, Samuel ([S.l.] : ROUTLEDGE, 2021)
This book investigates the devastating impacts of the Boko Haram terrorist campaign in Nigeria, reflecting on the group's historical context, organizational dynamics, and emerging trajectories.Since its inception in 2002, Boko Haram's terrorist campaign has become one of the major threats to security and human development in West Africa, killing tens of thousands of people, and displacing many more. This book reflects on the origins and development of Boko Haram, contextualizing it in the global trend of militant Islamist movements. It delves into the tactics of the organization, their deployment of sexual and gender- based violence against women and human rights abuses in the war against them. The war against Boko Haram has seen engagement from the international community, national and regional military operations, and also a range of civilian- led movements. This book reflects on the roles of these different actors, and the emerging trajectories that need to be considered in order to eradicate Boko Haram.Drawing on a range of disciplinary perspectives, this book will be of interest to researchers across the fi elds of sociology, political science, African studies, and peace and conflict studies.
OCLC-licensed vendor bibliographic record.
Keywords: POLITICAL SCIENCE / Political Freedom & Security / Terrorism; Boko Haram; Terrorism -- Nigeria; Violence -- Nigeria -- Religious aspects -- 21st century; Islamic fundamentalism -- Nigeria